2014
DOI: 10.3168/jds.2013-7368
|View full text |Cite
|
Sign up to set email alerts
|

Imputation of genotypes from low density (50,000 markers) to high density (700,000 markers) of cows from research herds in Europe, North America, and Australasia using 2 reference populations

Abstract: Combining data from research herds may be advantageous, especially for difficult or expensive-to-measure traits (such as dry matter intake). Cows in research herds are often genotyped using low-density single nucleotide polymorphism (SNP) panels. However, the precision of quantitative trait loci detection in genome-wide association studies and the accuracy of genomic selection may increase when the low-density genotypes are imputed to higher density. Genotype data were available from 10 research herds: 5 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 31 publications
0
27
0
1
Order By: Relevance
“…2). This has already been done in some studies in which, only genotypes that had a GC score higher than 0.60 were retained [6]. …”
Section: Discussionmentioning
confidence: 99%
“…2). This has already been done in some studies in which, only genotypes that had a GC score higher than 0.60 were retained [6]. …”
Section: Discussionmentioning
confidence: 99%
“…Data from the DFR cattle were supplemented with data originating from studies with four other Dutch breeds (Maurice‐van Eijndhoven ; Pryce et al . ; Maurice‐Van Eijndhoven et al . ) .…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have evaluated imputation accuracy for Bos taurus beef and dairy cattle breeds (Brøndum et al, 2012;Khatkar et al, 2012;Hozé et al, 2013;Ma et al, 2013;Pryce et al, 2014;Sargolzaei et al, 2014;Schrooten et al, 2014). However, to our knowledge, only a few imputation studies have been undertaken and reported in indicine cattle breeds (Bolormaa et al, 2013;.…”
Section: Imputation Accuracy With Different Snp Chipsmentioning
confidence: 99%